The Order of Things. Analysis and Sketch Study in Two Works by Steve Reich - Twila Bakker; Pwyll ap Siôn (Zeitschrift der Gesellschaft für Musiktheorie)
This article explores the boundaries that lie between analysis and sketch study, as found in two works by American composer Steve Reich (b. 1936). The article begins by examining the relationship between analysis and sketch study in relation to minimalist music. From this initial overview, the authors propose that one of the dangers intrinsic to sketch study—not saying anything particularly revealing about the musical work—can also be found in musical analysis. To combat this inherent weakness, the article advocates what William Kinderman has described as an “‘integrated approach’ whereby musical analysis takes guidance from sources” (2009, 7). Kinderman’s “integrated” approach is applied during the second half of the article, when two case studies relating to Reich’s compositions— both of which have previously received detailed analytical attention by other scholars—are examined in more detail. In analyzing Reich’s music, these scholars did not have access to the wealth of sketch materials now housed at the Paul Sacher Stiftung (PSS) Basel. In the first case study, John Roeder’s account, published in 2003, of the first movement of Reich’s popular New York Counterpoint (1985) is read against the authors’ own research of the composer’s extant sketches held at PSS. Likewise, a second case study examines Ronald Woodley’s article, published in 2007, of Reich’s Proverb (1996) in relation to the work’s sketch materials. The article will conclude by noting that while sketch studies should not be viewed as a kind of “holy grail”—revealing hidden truths or inner meanings about a work and unlocking the door to the composer’s inner thoughts and working processes—the working documents can (and do) offer insights that analysis does not always provide.